Enhanced Performance of Nano γ-MnO2/Mesocarbon Microbeads Composite as Electrocatalyst for Solid State Zinc-Air Cells. - ZHANG, SHENG-TAO; ZHANG, GUO-QING (Asian Journal of Chemistry, 2010)
Nanostructured γ-MnO2/MCMB (mesocarbon microbeads) composite has been prepared as electrocatalyst for application in solid-state zincair cell. Scan electronic microscopy and X-ray diffraction show that the MnO2 uniformly covers on the surface of MCMB with the typical γ-MnO2 composition. The electrocatalytic activity of the composite for oxygen electrode was examined by cathode polarization curve, chronoamperometry and electrochemical impedance spectroscopy (EIS). Results indicate that the electrocatalytic activity for oxygen reduction of the composite is better than that of single γ-MnO2. All solid-state zinc-air cell fabricated using this electrocatalyst exhibits good discharge performance. An energy density of 320 wh kg-1 was obtained with a power density of 27.4 w kg-1 at discharge current of 10 mA cm-2. The γ-MnO2/MCMB composite has potential application in zinc-air cells.